Application of bone transgenic zebrafish in anti‐osteoporosis chemical screening. Issue 1 (19th April 2018) - Huang, Hong‐xin; Lin, Hao; Lan, Fen; Wu, Yong‐fu; Yang, Zhen‐guo; Zhang, Jing‐jing
Abstract: Background: The zebrafish ( Danio rerio ) has recently been shown to be an ideal model to study bone disease including osteoporosis. The zebrafish osteoporosis model could be induced by glucocorticoid treatment with chemical staining for reflecting the level of bone mineralization. However, this methodology was unstable. Here, we developed a novel methodology to directly evaluate the bone mass and density. Methods: We generated and used the bone of transgenic zebrafish Tg ( ola.sp7:nlsGFP ) to evaluate the bone mass and density by measuring the areal extent and the integrated optical density (IOD) of enhanced green fluorescent protein (eGFP). This methodology was further compared with the traditional chemically stained method showing the bone mineralization. Furthermore, genes related to zebrafish osteoporosis were analyzed by quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR). Results: Our results of new methods were consistent with those from chemically stained fish, following glucocorticoid‐induction or epimedium flavonoid (FE)‐rescue treatments. qRT‐PCR analyses on mRNA levels revealed that glucocorticoid induces osteoporosis by downregulating the expression of osteoblast‐related factors osterix, osteocalcin, and osteopontin, and upregulating the expression of osteoclast‐related factor tartrate‐resistant acid phosphatase. In FE‐rescued fish, the expression of osteogenic factors osterix, osteocalcin, and osteopontin were increased. Conclusion: Compared to the traditional chemical staining methods, the new osteoporosis model using Tg( ola.sp7:nlsGFP ) is more convenient and efficient for studying osteoporosis in vivo, and especially for high‐throughput anti‐osteoporosis drug screening.